STRATEGI KEPALA MADRASAH DALAM MENGELOLA KONFLIK TENAGA KEPENDIDIKAN - Dinata, Yuriyan; Yuliharti; Setyaningsih, Rini (Department of Islamic Education Management, 2024)
This research examines the strategy of madrasah heads in managing educational staff conflicts at the Nurul Hidayah Sungai Salak Private Aaliyah Madrasah, Indragiri Hilir Regency. The aim is to describe conflict management strategies to increase work productivity and identify the obstacles faced. Using qualitative methods with a case study approach, through descriptive observation and interviews. The research results show that the madrasa head's strategy is influenced by the human relations paradigm, using avoidance, accommodation and compromise strategies, but the impact of conflict is not always positive because there is no effort to maintain optimal conflict levels. Obstacles include a lack of openness, silent conflicts, egoism, prestige, and feeling right. The recommended solution is to increase conceptual knowledge, develop competencies, and attend training.